2021
DOI: 10.1039/d1dt01945g
|View full text |Cite|
|
Sign up to set email alerts
|

Role of additives and solvents in the synthesis of chiral isoreticular MOF-74 topologies

Abstract: Chiral induction is a simple and inexpensive approach to synthesise chiral metal-organic frameworks, even when using achiral building-blocks. The challenge lies in selecting the proper chiral inductor. This can only...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…These factors can affect the final structures of crystalline materials. The importance of the solvent role relies on its template effect in the crystallization process. It has been shown that different MOFs can be achieved from the same ingredients by changing the kinds of solvents. , The solvent molecules can play their roles in the reactions by providing a reaction medium, coordinating to metal ions, and inhabitation in the voids of porous materials . Solvent molecules can coordinate with metal ions during the preparation of MOFs, which could affect the final structure by their structure-directing properties .…”
Section: Resultsmentioning
confidence: 99%
“…These factors can affect the final structures of crystalline materials. The importance of the solvent role relies on its template effect in the crystallization process. It has been shown that different MOFs can be achieved from the same ingredients by changing the kinds of solvents. , The solvent molecules can play their roles in the reactions by providing a reaction medium, coordinating to metal ions, and inhabitation in the voids of porous materials . Solvent molecules can coordinate with metal ions during the preparation of MOFs, which could affect the final structure by their structure-directing properties .…”
Section: Resultsmentioning
confidence: 99%
“…iii) The third approach is an indirect method that leads to the formation of achiral frameworks and utilization of some external chiral agents to produce stereogenic centres ( Xue et al, 2016 ; Zavakhina et al, 2019 ). Chiral inducing compounds may involve chiral guest, solvent, auxiliary pendant or functionalization ( Gheorghe et al, 2021 ). In this last case the presence of an enantiopure chiral agent is the driving force that induces chirality.…”
Section: Introductionmentioning
confidence: 99%